2020
DOI: 10.31025/2611-4135/2020.14003
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Odour Measurement Methods: The Odour Observatory as an Informative Tool for Citizen Science Based Approaches to Odour Management

Abstract: Odour pollution is a well-known problem related to a number of different industrial activities. It is also one of the main causes of citizens’ complaints to local authorities. Specific programs are needed to manage persistent odour pollution problems within communities in order to avoid possible socio-environmental conflicts. The H2020 project D-NOSES (Distributed Network for Odour Sensing, Empowerment and Sustainability) aims to help citizens co-create local solutions in collaboration with industries, regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…From the viewpoints of public health and air quality, the exhausts from rendering plants must be treated using a novel technology of high treatment efficiencies for reducing the long-standing complaints from community residents for the odors (Vieira et al, 2016;Sazakli and Leotsinidis, 2021;Sazakli et al, 2022). Chemical oxidation technology has been developed and widely applied for abating industrial odors over 30 years, especially for the odor emissions from various biological sources (Cheremisinoff, 1992;Capelli et al, 2019;Chou, 2009Chou, , 2019Wysocka et al, 2019;Zarra et al, 2019;Senatore, 2021). However, aldehydes emitted from the rendering processes have been seldom treated by a chemical oxidation system using hydrogen peroxide as an oxidant.…”
Section: Discussionmentioning
confidence: 99%
“…From the viewpoints of public health and air quality, the exhausts from rendering plants must be treated using a novel technology of high treatment efficiencies for reducing the long-standing complaints from community residents for the odors (Vieira et al, 2016;Sazakli and Leotsinidis, 2021;Sazakli et al, 2022). Chemical oxidation technology has been developed and widely applied for abating industrial odors over 30 years, especially for the odor emissions from various biological sources (Cheremisinoff, 1992;Capelli et al, 2019;Chou, 2009Chou, , 2019Wysocka et al, 2019;Zarra et al, 2019;Senatore, 2021). However, aldehydes emitted from the rendering processes have been seldom treated by a chemical oxidation system using hydrogen peroxide as an oxidant.…”
Section: Discussionmentioning
confidence: 99%
“…Different techniques, such as field inspection, electronic noses, and portable olfactometer, may be used to determine odor concentrations in the ambient air. [ 21,22 ] There are several standard olfactory methods for measuring odor concentrations, such as the dynamic olfactometry method and the triangle odor bag method. [ 23 ] These methods have advantages and disadvantages, and the choice of methodology depends on the particular aims and needs of the research.…”
Section: Methodsmentioning
confidence: 99%
“…Only three articles were found that dealt with citizen science projects to manage the odour pollution caused by industrial facilities [65][66][67]. Such articles were written by European scientists (from Italy, Spain, Hungary and The Netherlands).…”
Section: Regional Distribution Of the Papersmentioning
confidence: 99%
“…Firstly, as outlined by [66], public engagement in odour pollution can provide further knowledge about it, through the high numbers of "sentries". Collecting several citizen complaints about odours could be an advantage to identify efficiently the potential receptors and pathways of the gas pollutants, with reference to a specific industrial installation.…”
Section: Advantagesmentioning
confidence: 99%
See 1 more Smart Citation